Propuesta de Sistema de Apoyo al Aprendizaje (SAPA) aplicado a las materias de Inteligencia Artificial y Arquitectura de Computadores que se dictan en la Titulación de Ingeniería en Informática, en la modalidad de estudios a distancia de la Universidad Técnica Particular de Loja. - Jaramillo Galárraga, Boris Vladimiro (2014)
In this thesis work it analyzes the current progress and applications of the Help Systems, Recommender Systems and Personal Assistants, as a basis for developing a proposal for a Learning Support System, which could be applied on the current informatic platform that supports the teaching online of Virtual Learning Environment (VLE) developed in Moodle, for the subjects of Artificial Intelligence (9no. Cycle) and Computer Architecture (5th cycle) of Engineering Degree in Computer Science, in the Open Distance Modality (ODM) of the Particular Technical University of Loja (UTPL, for its acronym in spanish). It has done careful analysis of the most useful helps and recommendations on-line for these subjects according to the current conditions of distance learning of the UTPL and its contents. It implemented a simulation in line to visualize and test this proposed of system within a particular EVA, which determined by a Learning Style Test the personalized path of e-Learning (weekly sequence of Learning Objects) to be followed by each students throughout a semester.